Educational innovation in elementary school: a bibliometric analysis - Johanna Gallego Alvarez; Lina Rosa Parra Bernal; Vladimir Henao Céspedes (Institute of Advanced Engineering and Science, 2025)
This article presents the results of a bibliometric analysis to answer the research question: What educational innovations have been applied worldwide and published in articles in indexed journals? There were 83 Scopus records obtained, of which, after applying the preferred reporting items for systematic reviews and meta-analyses (PRISMA) methodology, 6 were excluded, obtaining a total of 77 articles for analysis. This analysis focused on trends such as annual productivity, geographic distribution, most relevant journals, thematic areas, and co-occurrence of author keywords. Subsequently, a review of the 10 most relevant articles on the subject was carried out. A decrease in productivity was observed during 2021, the year after the COVID-19 pandemic. Additionally, educational innovation has been articulated with different areas of knowledge. The analysis of the documents highlights the need to train teachers in using tools that facilitate the integration of educational innovation in the classroom. It is recommended that future studies based on the geographic distribution of academic productivity explore the different experiences these countries have had in incorporating educational innovation in the classroom and analyze the public policies that have promoted it.